2021
DOI: 10.1186/s12879-021-05989-w
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neighborhood census-tract level socioeconomic status and respiratory syncytial virus-associated hospitalizations in U.S. adults, 2015–2017

Abstract: Background Respiratory syncytial virus (RSV) infection causes substantial morbidity and mortality in children and adults. Socioeconomic status (SES) is known to influence many health outcomes, but there have been few studies of the relationship between RSV-associated illness and SES, particularly in adults. Understanding this association is important in order to identify and address disparities and to prioritize resources for prevention. Methods Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Though the epidemic dynamics of RSV vary even within local geographic areas [5,6], little is known about how the burden of RSV varies between populations. Previous research has had mixed conclusions about the impact of socioeconomic status (SES) on the risk of RSV infections [7][8][9]. While some studies found lower rates of RSV infection in higher SES groups, others found no relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Though the epidemic dynamics of RSV vary even within local geographic areas [5,6], little is known about how the burden of RSV varies between populations. Previous research has had mixed conclusions about the impact of socioeconomic status (SES) on the risk of RSV infections [7][8][9]. While some studies found lower rates of RSV infection in higher SES groups, others found no relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In the last four years, several systematic reviews and meta-analyses were published [ 15 , 16 , 17 , 25 , 27 , 29 , 31 , 32 , 41 ], most of them with the aim to define the disease burden of RSV in older adults and some of them with the active participation of pharma companies involved in RSV vaccine and drug development. Several clinical studies have been published over the years worldwide [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. In Europe, what emerged together with the findings of few multicenter clinical studies [ 21 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] was the need to harmonize and collaborate between the various laboratories in order to obtain shared diagnostic protocols with which to compare data...…”
Section: Can We Consider Rsv a Forgotten Pathogen In Older Adults?mentioning
confidence: 99%
“…There is broad consensus that, on average, residents from socially and economically deprived neighborhoods experience worse health outcomes than those from more prosperous areas [ 12 ]. Studies have found that residents of high-poverty areas suffer from higher rates of heart disease [ 13 ], respiratory ailments [ 14 ], cancer [ 15 ], and overall mortality [ 12 ]. A socially deprived neighborhood is often characterized by poor infrastructure and insufficient medical resources, which may be associated with serious adverse health outcomes for residents [ 16 ].…”
Section: Introductionmentioning
confidence: 99%